Paramagnetic spherical nanoparticles by the self-assembly of persistent trityl radicals. Issue 4 (8th January 2016) - Marin-Montesinos, I.; Paniagua, J. C.; Peman, Alejandro; Vilaseca, M.; Luis, F.; Van Doorslaer, S.; Pons, M.
Abstract : The self-association of a water-soluble persistent trityl radical gives rise to paramagnetic nanoparticles: a new class of non-metallic high spin systems. Abstract : Spherical nanoparticles and fibres observable by cryo-electron microscopy are spontaneously formed by the Finland trityl radical at concentrations above 15 mM. These species represent a new class of paramagnetic, metal-free, nanoscale supramolecular materials. Self-association was observed under a variety of experimental conditions, including aqueous solution at room temperature, low temperature frozen glasses and the gas phase. Oligomers formed by at least 5 Finland radicals were detected by ion-mobility mass spectrometry. Magnetic susceptibility data as well as low temperature EPR spectra show coupling between electronic spins in the self-assembled species. Quantum chemical calculations show stacking along the C 3 symmetry axis. Nanoparticle formation requires additional lateral packing that can be provided by hydrogen bonding involving the triangular array of carboxylic acid groups leading to the assembly of geodesic spheres.